Physical therapy for sleep apnea: a smartphone application for home-based physical therapy for patients with obstructive sleep apnea - Bui-Diem, Khue; Hung, Ching-Hsia; Zhu, Guan-Cheng; Tho, Nguyen Van; Nguyen-Binh, Thu; Vu-Tran-Thien, Quan; To-Truong, Duy; Ngo-Thanh, Hoan; Duong-Quy, Sy (Frontiers in Neurology, 2023)
Purpose In this study, we described PT for Sleep Apnea, a smartphone application for home-based physical therapy of patients with Obstructive Sleep Apnea. Methods The application was created in a joint program between University of Medicine and Pharmacy at Ho Chi Minh City (UMP), Vietnam and National Cheng Kung University (NCKU), Taiwan. Exercises maneuvers were derived from the exercise program previously published by the partner group at National Cheng Kung University and included exercises for upper airway and respiratory muscle training and general endurance training. Results The application provides video and in-text tutorials for users to follow at home and a schedule function to assist the user in organizing the training program, which may improve the efficacy of home-based physical therapy in patients with Obstructive Sleep Apnea. Conclusion In the future, our group plans to conduct user study and randomized-controlled trial to investigate whether our application can benefit patients with OSA.